Erosion-like and dilation-like operators applied to the image processing of pigmented skin lesions - Mollinedo, Arturo (2019)
This paper studies the algorithm presented in [4] by recreating it and applying to images of pigmented skin lesions. In the future, it is expected to avoid gray scale transformation of images of pigmented skin lesions during their preprocessing therefore maintaining the vitally important information of colored images and preserving the benefits introduced by the application of these operators.The performance of these local extensionsis quantified to determine in conclusion, that the difference between their application and gray scale image processing is not significant hence the opening and closing operators can be used in color image preprocessing without creating false colors.